What Is a Good Job? - Werner Eichhorst; Florian Wozny; Erno Mähönen (Institute for the Study of Labor (IZA), 2015)
After the apparent rise of so-called atypical and 'precarious' jobs, the quality of employment has become of interest because such employment relationships are often related to objectively or subjectively worse working conditions. In this paper we look in detail into what is known about job quality, what kinds of effects it has on job satisfaction, and how the quality of jobs has changed in the past by assessing objective and subjective indicators for different educational groups. Results show that a general negative trend in the development of work quality cannot be observed, neither for 'hard' indicators such as the share of temporary employment or unusual working time nor for 'soft' indicators like job satisfaction or perceptions about job security. Developments are rather country-specific, and even within countries differences occur between educational groups.
Keywords: J21; J28; 330; quality of employment; good jobs; non-standard work; job satisfaction